A complicated case of whole-lung lavage: a case report - Petrarulo, Simone; Lucchin, Manuel; Oldani, Stefano; Dubini, Alessandra; Piciucchi, Sara; Gori, Alberto; Aiello, Luca; Maitan, Stefano; Spagnolo, Paolo; Ravaglia, Claudia; Poletti, Venerino (Frontiers in Medicine, 2023)
Introduction We report a life-threatening case of severe respiratory failure due to a pulmonary alveolar proteinosis (PAP) secondary to lysinuric protein intolerance (LPI), complicated by a pre-existing right pneumothorax, which we treated using a rescue whole-lung lavage (WLL). To date, in the literature, there are no cases of WLL performed in this condition. Clinical condition Patient was referred to our center because of rapidly worsening dyspnea and deterioration of gas exchange, caused by a secondary form of PAP which required an immediate therapeutic option such as the one offered by WLL. On physical examination, bilateral crackles were present, and peripheral blood oxygen saturation was 78% on oxygen with a FiO2 of 40%. Interventions After stabilizing the clinical conditions with oxygen therapy erogated through a high-flow nasal cannula, shortly after admission, we performed a rescue WLL among two procedures. The procedure was very effective, and the patient was later discharged without oxygen therapy and in good clinical condition. Conclusion Our case report represents a chance to help fill the gap of knowledge relative to secondary forms of PAP. The patient we presented suffers from a very rare genetic condition (LPI) that only has a few reported cases in the literature and has a very low prevalence which makes it difficult to produce the affected people:newborns ratio. We believe that difficult and rare cases like this one can improve our understanding of the disease and, most importantly, of how much the only therapeutic option we had, a rescue WLL, is effective to improve gas exchange and radiological features, despite being performed in these severe respiratory conditions.